The importance of school and academic context in educational performance in a sample of Portuguese adolescents - Pestana, Leonor (2017)
The school/academic context is key in engaging students in the learning process and consequently on school performance. Which academic and school context variables influence school performance (study environment, study planning, study method, reading skills, motivation to study, overall school performance) in adolescent? To assess the association between variables - school success, school environment, academic - and school performance in Portuguese adolescents from a sample of the central region. A quantitative, cross sectional, correlational study. Data collected through questionnaire of direct administration (sociodemographic, academic and school context variables and school performance scale). Non-probabilistic convenience sample of 380 students of 7th, 8th and 9th years of education in the school year 2011/2012, from a 2nd and 3rd cycle Basic School of Viseu Municipality, Portugal. Teens who have never failed (p <0.001), who live closer to school (p = 0.007) and who spend less time traveling to school (p = 0.007) are those who have a better overall school performance. A better school performance is also achieved, in the study planning (p = 0.015) dimension, by the adolescents with fewer years of schooling. Academic and school context variables, like the grade attended by adolescents, the distance they live from the school, and the time taken in traveling to school, are determinants of adolescent school performance.